2013
DOI: 10.1021/jf402854b
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Formation of Trans Fatty Acids under Heating Conditions in Triolein

Abstract: To elucidate the relationship between heat-induced cis/trans isomerization and reaction temperature and energy in unsaturated lipids, we investigated the molecular mechanism of the heat-induced cis/trans isomerization of 18:1 isomers. Triolein (18:1,9c) was heated at two range temperatures (130, 160, 190, 220 °C and 135, 140, 145, 150, 155 °C) and analyzed by the gas chromatography (GC) method. When the heating temperature increased to 150 °C, the amount of trans 18:1n-9 changed from 0.0897 mg/g oil (1 h) to 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…This indicates that the structural (positional) isomerization and geometrical isomerization in which the cis isomers of fatty acids in margarine is stable and not affected by applied heat treatment at 120°C. It was reported previously that cis isomerization to trans may occur at 150°C [14]. The results are in accordance with these results where it was found that the amount of elaidic acid in margarine heated at 150, 190 and 250°C varies with time in which there is a cubic nonlinear significant relationship between percentage of elaidic acid and time of heating.…”
Section: Elaidic Acid Formation In Margarinesupporting
confidence: 91%
“…This indicates that the structural (positional) isomerization and geometrical isomerization in which the cis isomers of fatty acids in margarine is stable and not affected by applied heat treatment at 120°C. It was reported previously that cis isomerization to trans may occur at 150°C [14]. The results are in accordance with these results where it was found that the amount of elaidic acid in margarine heated at 150, 190 and 250°C varies with time in which there is a cubic nonlinear significant relationship between percentage of elaidic acid and time of heating.…”
Section: Elaidic Acid Formation In Margarinesupporting
confidence: 91%
“…Although the change of every type of trans fatty acid was fluctuant, the range of this variation was not very great during extrusion with increasing temperature. Since the cis- to trans -isomerization may occur at 150°C [23], the formation of trans fatty acids was likely exacerbated by the combined effects of pressure and high temperature. A previous study reported that only 1% to 2% of the unsaturated fatty acids were converted to the trans -form during the extrusion of cornmeal [16, 24].…”
Section: Resultsmentioning
confidence: 99%
“…This paper demonstrates that the temperature of isomerization of linoleic acid is 140 C, and the temperature for oleic acid is 150 C, as was shown by our laboratory previously. 22 This indicates that linoleic acid is more prone to isomerization than oleic acid under heat treatment.…”
Section: Quantum Chemistry Calculation Analysis Of Isomerizationmentioning
confidence: 99%
“…It has been applied to study the mechanism of trans fatty acids under heating conditions in triolein by our research team. 22 The purpose of this paper is to study the isomerization temperature of linoleic acid and to determine the type and content of trans linoleic acid at various temperatures. The cis/ trans isomers were determined by HPLC and the decomposition products were determined by GC.…”
Section: Introductionmentioning
confidence: 99%